2016
DOI: 10.1016/j.jff.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of whey alters atrophy, gene expression profiles and dysfunction of salivary glands in elderly rats

Abstract: Salivary glands in elderly individuals commonly exhibit morphological changes and dysfunction resulting in xerostomia. Long-term (4-week) drinking of whey prevented and/or restored age-dependent decline of salivary volume and protein concentration, and atrophy of sublingual glands (SLGs) significantly in 88-week-old rats. The transcripts of 42 genes were up-regulated and 7 genes were down-regulated by more than 1.5-fold change with FDR ≦ 0.1 after whey-drinking. The expression levels of genes associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…LHK treatment induced the expression of the Tcfap2β gene in salivary glands. As reported previously, whey consumption induces Tcfap2β expression [17]. The AP-2 family of transcription factors consists of five members, AP-2α, 2β, 2γ, 2δ, and 2ε, each encoded by a separate gene [34], and is known to have tissue-specific expression to regulate the expression of other genes [23].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…LHK treatment induced the expression of the Tcfap2β gene in salivary glands. As reported previously, whey consumption induces Tcfap2β expression [17]. The AP-2 family of transcription factors consists of five members, AP-2α, 2β, 2γ, 2δ, and 2ε, each encoded by a separate gene [34], and is known to have tissue-specific expression to regulate the expression of other genes [23].…”
Section: Discussionmentioning
confidence: 71%
“…We previously reported that the administration of whey from the milk of Jersey cattle mitigates age-dependent atrophy and functional decline of salivary glands accompanied with changes in gene expression [17]. The major components of whey proteins are of β-lactoglobulin, α-lactalbumin, bovine serum albumin, and immunoglobulin, representing 50%, 20%, 10% and 10% of the whey fraction, respectively [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that the administration of whey from Jersey cow milk mitigates age-dependent atrophy and functional decline of salivary glands accompanied with changes in gene expression in rats (12). We found that the bioactive peptides, which were LLHK, LHK, and HK derived from β-lactoglobulin C variant, prevent and / or restore the age-depending decline in structure and function of salivary gland (15).…”
Section: Discussionmentioning
confidence: 88%
“…We previously reported that the administration of whey from Jersey cow milk mitigates the age-dependent atrophy and functional decline of rat salivary glands, accompanied with changes in gene expression (12). β-Lactoglobulin A and B are the most common variants, while the β-lactoglobulin C variant is observed in Jersey cattle.…”
Section: Introductionmentioning
confidence: 99%